The role of group projects in enhancing soft skills - Vijaya Bhaskar C; Sujatha Priyadharshini P.R.; Prabha Govindharaj; Praveen Sam D (Humanities & Social Sciences Communications)
Abstract In today’s world, soft skills are key to success for engineers in the workplace. Desirable characteristics for graduates are outlined by various accrediting boards, which include proficiency in communication, competence to collaborate in multidisciplinary teams, and a tenacity to learn throughout the life. Indeed, language courses that engineering students take in their first and third years in India are designed to enhance their ability to collaborate effectively and express their ideas clearly. The objective of this study is to figure out how well students demonstrated their soft skills when working on group projects while pursuing the elective course “Film Appreciation”. A total of 123 second-year students from various engineering courses participated in this study. As part of the assessment, students are required to submit two group projects, a written assignment and a short film with a duration of two to three minutes, for the first and second assessments. In this study, we focus only on students’ experiences in making short films. Teachers used a mixed-method approach that includes questionnaires and semi-structured interviews to collect responses from students regarding their demonstration of soft skills during the group projects. The study reveals that the students demonstrated a solid understanding of soft skills and effectively applied them during the group project. It is clear that group projects in elective classes are instrumental in helping students demonstrate the essential soft skills, such as persuasive skills, group discussion skills, leadership, problem-solving, time management, etc. However, the challenges students faced during this project imply that they require additional support from the teachers to ensure they could avoid repeating the same mistakes in future group projects.